Effects of Arabika Coffee (Coffea arabica L.) Pulp Extracts on Anopheles sp. Larva Mortality - Husna Fitri; Rizma Nurul Akhlas; Liana Fairuzannah Mahdiana; Rita Maliza (Jurnal Biologi Tropis, 2023)
Malaria is one of the main public health problems in Indonesia. Anopheles sp. mosquito larvae is vector of malaria that must be treated before it develops into a mosquito. Control of larvae by using larvicides containing hazardous chemicals causes side effects on the environment and resistance. This study aimed to determine the effect of giving the Arabika Coffee (Coffea arabica L.) pulp extracts on the mortality of Anopheles sp. larvae. Arabika coffee pulp extracts was fractionated with polar, semi-polar and non-polar. This study used ten larvae of Anopheles sp. Observations of larval mortality were carried 24 hours with five concentration series (0, 125, 250, 500, and 1000 ppm). The results of the mortality test showed that non-polar fraction of Arabika coffee pulp extracts had the highest larvicidal activity with values of LC50 and LC90, 278 ppm and 22950 ppm. In semi-polar and polar fractions, the LC50 and LC90, 1718 and 92683 ppm, 34085 and 40862 ppm were obtained. The results of compound analysis obtained 16 active compounds from non-polar extract of arabika coffee pulp with the five highest compounds, namely Hexadecanoic acid, 9,12-Octadecadienoic 15-Octadecenoic acid, Octadecanoic acid and 3-Furanacetic acid. Non-polar fraction of arabika coffee pulp extracts had larvicidal activity against Anopheles sp.